Pensamientos distorsionados y su incidencia en la depresión de un adulto mayor en tiempos de pandemia - Salcedo Arcentales, Ida (2020)
The case study is about an older adult who presents problems in his depressed mood, the objective of this work is to know the incidence that distorted thoughts have on the depressed state of an older adult, to modify them and thus have a good mental health, for this it has been chosen to work with the line of research of the degree entitled "treatment of learning problems", the sub-line of research is "interpersonal and group conflicts of teachers affect the practice of human relations of the educational community ”. The direct beneficiaries of this research work are: the student and the patient; the indirect beneficiary is the company; The students will put into practice all the theories they have read and learned, here is the time to look for the best strategy for the patient to get out of the emotional state in which they are in order to feel good and can relate to other individuals. Excessive worry causes fear, fear, uncertainty, sadness, overwhelm in the face of the circumstances that currently surround people, many times that depression is the product of worry and the presence of automatic thoughts which interferes in their life and in the life of those around you.